Sustainability analysis : visitors impact on Taman Negara, Pahang, Malaysia / Nor’Ain Othman, Nor Asmalina Mohd Anwar & Lim Lay Kian - Nor’Ain, Othman; Nor Asmalina, Mohd Anwar; Lim, Kian Lay (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, 2010)
The aim of this research paper is to measure the sustainability of the Taman Negara (National Park) using the Visitors Impact Management (VIM) approach from the visitors’ perspectives on environmental impacts and the management of the Park. VIM aims to reduce or control the impacts that threaten the quality of outdoor recreation and tourism areas and experiences. The objectives of the study are to assess the impact of domestic and international visitors, to identify visitor’s experiences and opinions on the park activities and facilities and recommend and improve the potential management actions and develop strategic planning for developing and sustaining Taman Negara. A total of 313 international tourists were surveyed and asked to indicate their perceptions and experiences during their visit and the types of activities in which they participated in Taman Negara. Researchers carried out personal interviews with the park officials and a field survey was conducted in April and October 2007 and March 2008. The analysis reveals that the visitors enjoyed their experiences on a canopy walkway, jungle trekking and hiking, night jungle walks, cave exploration, a visit to an aborigine settlement and rapid shooting. Their main concerns were the natural environmental conditions, especially the damage to the park due to too many people, soil erosion, littering, provocation of wildlife and vegetation damage along walk trails. Visitors supported park management in limiting the number of visitors, the number of people in a group and better educating visitors about conservation. They agreed that the staff at the park should provide more information on the park through brochures and assist the visitors.